2021
DOI: 10.30539/ijvm.v45i2.1257
|View full text |Cite
|
Sign up to set email alerts
|

2-Deoxyglucose Glycolysis Inhibitor Augment Oncolytic Virotherapy to Induce Oxidative Stress and Apoptosis in Breast Cancer (Part Ⅲ)

Abstract: One of the "hallmarks of cancer" is altered energy metabolism, which is increased glycolysis in cancer cells, the primary source of energy that uses this metabolic pathway to generate ATP. Oncolytic virotherapy with aerobic glycolysis inhibitor smart therapeutic approach to induce apoptosis in cancer cells. The current study aimed to use the 2-Deoxyglucose (2DG), a specific glycolysis inhibitor, to enhance the Newcastle disease virus (NDV). In this study, a mouse model of breast cancer allograft with mammary a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
1
0
0
Order By: Relevance
“…A decline in the pentose phosphate pathway accompanies glucose deprivation, dysfunction of glutathione synthesis and ROS accumulation, and a decrease in the NADPH and intracellular GSH (Zhu et al, 2020). The present study finding is consistent with previous works that reported NDV inhibition of glutathione synthesis, underexpression of glutathione peroxidase, and accumulation of ROS in tumor cells (Kan et al, 2021;Obaid et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…A decline in the pentose phosphate pathway accompanies glucose deprivation, dysfunction of glutathione synthesis and ROS accumulation, and a decrease in the NADPH and intracellular GSH (Zhu et al, 2020). The present study finding is consistent with previous works that reported NDV inhibition of glutathione synthesis, underexpression of glutathione peroxidase, and accumulation of ROS in tumor cells (Kan et al, 2021;Obaid et al, 2021).…”
Section: Discussionsupporting
confidence: 92%